2021
DOI: 10.1016/j.isci.2021.103522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene-gene interactions associated with cancer onset and progression are largely independent of changes in gene expression

Abstract: Summary Recent findings indicate that changes underlying cancer onset and progression are not only attributable to changes in DNA structure and expression of individual genes but to changes in interactions among these genes as well. We examined co-expression changes in gene-network structure occurring during the onset and progression of nine different cancer types. Network complexity is generally reduced in the transition from normal precursor tissues to corresponding primary tumors. Cross-tissue ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Overall, we found that genes displaying significant changes in gene-gene connections in the transition from normal to cancer cells were often not differentially expressed. This observation was consistent across different cancer types [Figure 2 in ( Arshad and McDonald, 2021 )].…”
Section: Expected Outcomessupporting
confidence: 72%
See 4 more Smart Citations
“…Overall, we found that genes displaying significant changes in gene-gene connections in the transition from normal to cancer cells were often not differentially expressed. This observation was consistent across different cancer types [Figure 2 in ( Arshad and McDonald, 2021 )].…”
Section: Expected Outcomessupporting
confidence: 72%
“…Of these, 297 edges in cancer and 2261 edges in normal were consistently found in each model iteration and these conserved edge lists were used to define our final consensus networks. Figure 1 in the study by ( Arshad and McDonald, 2021 ) presents results for this overall reduction in network complexity observed in nine different cancer types, including LUSC.…”
Section: Expected Outcomesmentioning
confidence: 99%
See 3 more Smart Citations